Uji Aktivitas Antibakteri Sediaan Mouthwash Dari Ekstrak Daun Peppermint ( Mentha piperita L.) dan Daun Jarak Cina ( Jatropha multifida L.) Terhadap Streptococcus mutans - Putri , Adilla; Nasution, Muhammad Amin; Lubis , Minda Sari; Nasution, Haris Munandar (Journal of Pharmaceutical and Sciences, 2025)
Background: Mouthwash is a liquid preparation that plays an important role in maintaining oral health. An ideal formulation should possess antibacterial effectiveness, physicochemical stability, and acceptable organoleptic properties. Streptococcus mutans is the primary pathogenic bacterium responsible for halitosis and dental caries. Peppermint (Mentha piperita L.) and physic nut (Jatropha multifida L.) leaves are known to contain bioactive compounds such as flavonoids, saponins, and tannins, which have potential antibacterial activity. Objective: This study aimed to formulate peppermint and physic nut leaf extracts into a stable mouthwash preparation and evaluate its antibacterial activity against Streptococcus mutans. Methods: The extracts were prepared using maceration with ethanol as a solvent. The mouthwash formulations were developed with three variations of extract concentrations (2%, 2.5%, and 3%). The preparations were then evaluated for their physical stability (organoleptic properties and pH) and tested for antibacterial activity against S. mutans using the Kirby-Bauer disc diffusion method. Inhibition zone data were statistically analyzed using ANOVA and Duncan’s test. Results: Physicochemical evaluation showed that all formulations remained stable over 28 days of observation, with a pH of 6, which is compatible with the oral cavity. Antibacterial testing demonstrated an increase in inhibition zone diameter with higher extract concentrations: 10.33 mm (2%), 11.1 mm (2.5%), and 11.9 mm (3%). These results were comparable to the positive control, Betadine gargle (11.95 mm). The negative control showed no inhibition zone. Statistical analysis revealed significant differences (p < 0.05) among the concentrations. Conclusion: The combination mouthwash containing peppermint and physic nut leaf extracts at a concentration of 3% was found to be the most stable formulation and exhibited the strongest antibacterial activity, comparable to the commercial reference product. Thus, this combination extract has potential to be developed as a natural antibacterial agent for oral health.